Management of capital assets by local governments: an assessment and benchmarking survey - Kaganova, Olga; Telgarsky, Jeffrey (International Journal of Strategic Property Management, 2018)
There is a growing recognition of the importance of government-owned capital assets, both conceptually and in practice, in large part due to the 2008 global financial crisis. However, a sizeable gap remains between the academic and professional “universe of knowledge” surrounding government asset management, and the actual asset management practiced by governments. In particular, the majority of governments around the world are wholly uninformed when it comes to good asset management. The purpose of this paper is to reduce this gap and suggest an instrument specifically for local governments, for the evaluation of their asset management, in order to help them to identify the weakest elements of asset management and thus focus limited resources on improving these elements. The instrument consists of essentially a composite image of good asset management practices for three main asset types: buildings, land, and infrastructure. The instrument specifies each asset management practice by its key characteristics and then converts each characteristic into a survey question. Answers are scored and a total score for each asset type is calculated. The assessment instrument can be used by local governments, their advisers, and by researchers interested in comparative analysis of asset management in different jurisdictions or countries.